PENGARUH KEPEMIMPINAN DAN MOTIVASI ANAK ASUH TERHADAP KESEJAHTERAAN SOSIAL ANAK ASUH DI PANTI ASUHAN KURNIA ASIH BANDUNG - Bagianto, Agus; Yuniati, Yuniati (2018)
The research was done at Kurnia Asih Orphanage in Bandung. The cases was formulated as follow : are there the influence of leadership to ward the social welfare of the foster child and are there the influence of motivation of the foster child to ward the social welfare of the foster child, then are there the influence of leadership and the motivation of a foster child as simultanously to ward the social welfare of a foster child at Kurnia Asih Orphanage. The research methode used descriptive analysis and the application to operate has been used by SPSS.16 with the 50 population as respondent for all children who live in Kurnia Asih Orphanage. The data analysis technique has been used the cross tabulation statistic analysis to be seen from gender and the age of children and means one-way anova to be seen from levels of education and the status of the child. Then used the correlation analysis technique to know about correlationship degree among the research variabel and path analysis technique. The research of result that the leadership, motivation of the foster child and sosial welfare of the foster child variable is the best category. There are the influential a significant positive the leadership (X1) toward the social welfare of a foster child (Y) at Kurnia Asih Orphanage, has got 0,391 or 39,1%. There are the the influential a significant positive the motivation of a foster child (X2) toward the social welfare of a foster child (Y) at Kurnia Asih Orphanage, has got 0,413 or 41,3%. there are the influence of leadership (X1) and the motivation of a foster child (X2) as simultanously to ward the social welfare of a foster child (Y) at Kurnia Asih Orphanage, has got 0,545 or 54,5%. The Conclusion from this research is proved the influential a significant positive between the leadership (X1) and the motivation of the foster child (X2) toward social welfare of the foster child (Y) at Kurnia Asih Orphanage.